Customer Loyalty in Islamic Microfinance: The Role of Service Quality and Trust - Lailatul Maghfiroh (CV. Era Digital Nusantara, 2024)
This study examines the impact of service quality and trust on customer loyalty in BMT Trans Redjo Mulyo Dadi, Indonesia. Using survey data from 107 respondents and analyzed with SEM-PLS, the findings reveal that both service quality and trust significantly enhance customer loyalty. The novelty of this research lies in extending loyalty models to Islamic microfinance institutions, highlighting the critical role of trust and service quality in sustaining member commitment. This contributes to the global literature by offering empirical evidence from a developing-country context, where microfinance plays a vital role in financial inclusion and community empowerment.